RUANG BANACH SEBAGAI RUANG OPERATOR YANG DIBANGKITKAN OLEH FUNGSI TERUKUR DAN TERBATAS ESSENSIAL - Muslim A; sumanto sumanto (MATEMATIKA, 2010)
In this paper, we construct a new normed Banach space  from collection of all Carleman operators from Hilbert spaceinto Lebesgue space , denoted by  with respect to the norm for every  generated by an essensially bounded measurable function .